Analisis Normatif Tindak Pidana Pornografi (Studi Putusan No:46/Pid.Sus/2024//PN Jmb) - Hartono, M. Rudi; Prakoso, Vito Ronaldo Akbar (Universitas Batanghari Jambi, 2025)
The crime of pornography is an act that violates moral norms by producing, distributing, or possessing pornographic content, which is regulated in Law Number 44 of 2008 concerning Pornography. Violations of this law can be subject to criminal sanctions in the form of imprisonment and fines. The crime of pornography is a phenomenon that arises in society that can be committed by anyone and against anyone who becomes a victim. Amidst advances in technology and science, the crime of pornography can also occur with the support of internet technology through social media accounts. Social media users are also expected to be wise in using available applications so as not to cause negative impacts and losses to others, especially in loading, distributing, transferring content containing pornographic elements. Of course, for anyone who commits pornographic acts must be responsible for their actions in accordance with applicable legal provisions, of course through the criminal justice system from the investigation process at the Police to the trial in Court until a judge's decision is made to determine whether someone is found guilty or not. The method used in this study is a normative juridical research type, while the approach used in this study is a case study approach. The data collected in this study was sourced from literature. The conclusion of this study is that the verdict handed down by the judge against the perpetrator of the pornography crime in this case study lacks a sense of justice and legal certainty. The judge failed to consider other elements in his considerations, thus making the application of the article inappropriate.